Effect of gamma-alumina nanorods on CO hydrogenation to higher alcohols over lithium-promoted CuZn-based catalysts - Choi, SuMin; Kang, YoungJong; Kim, SangWoo (ELSEVIER SCIENCE BV, 2018)
To achieve high catalytic activities and long-term stability to produce higher alcohols via CO hydrogenation, the catalytic activities were tuned by controlling the loading amounts of gamma-alumina nanorods and Al3+ ions added to modify Cu-Zn catalysts promoted with Li. The selectivity of higher alcohols and the CO conversion to higher alcohols over a Li-modified Cu0.45Zn0.45Al0.1 catalyst supported on 10% nanorods were 1.8 and 2.7 times higher than those with a Cu-Zn catalyst without nanorods and Al3+ ions, respectively. The introduction of the thermally and chemically stable gamma-Al2O3 nanorod support and of Al3+ to the modified catalysts improves the catalytic activities by decreasing the crystalline size of CuO and increasing the total basicity. Along with the nanorods, a refractory CuAl2O4 formed by the thermal reaction of CuO and Al3+ enhances the long-term stability by increasing the resistance to sintering of the catalyst.
Keywords: ZN-AL; SYNGAS; ETHANOL; OXIDE; CONVERSION; SURFACE; SYSTEM; CNTS; FE